2005
DOI: 10.1007/s00198-005-1928-y
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of N-methyl D-aspartate receptor in rat-modeled disuse osteopenia

Abstract: Lack of mechanical stress may result in osteoporosis; however, the underlying mechanisms of disuse osteoporosis remain unclear. It has been indicated that mechanical loading causes extracellular glutamate accumulation in osteoblasts. We hypothesized that the glutamate receptor mediation on bone cells might also be involved in mechanically stimulated osteogenesis. In this study, we investigated the changes of bone formation and the expressions of osteogenic genes and N-methyl D-aspartate (NMDA) receptors, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Taiwanese women used to be known to have femoral neck bone mineral density (BMD) values of 0%-15% lower than those of Caucasians. The vertebral fracture rate was 18% for women, whereas the hip fracture rate was 0.203% in 1996, which was lower than that in Caucasians and similar to those in Chinese and other Asian women [2][3][4][5]. However, the incidence appeared to be as high as 505 per 100,000 in a recent nationwide survey in Taiwan [6].…”
Section: Introductionmentioning
confidence: 78%
“…Taiwanese women used to be known to have femoral neck bone mineral density (BMD) values of 0%-15% lower than those of Caucasians. The vertebral fracture rate was 18% for women, whereas the hip fracture rate was 0.203% in 1996, which was lower than that in Caucasians and similar to those in Chinese and other Asian women [2][3][4][5]. However, the incidence appeared to be as high as 505 per 100,000 in a recent nationwide survey in Taiwan [6].…”
Section: Introductionmentioning
confidence: 78%
“…It has been reported that in vivo mechanical loading decreased the expression of ionotropic glutamate receptors in osteoclasts and bone lining cells (41). Meanwhile, mechanical unloading also decreased NMDA receptor in disuse osteopenia (42). These effects on the expression of glutamate receptors may cause changes in the sensitivity to mechanical loading.…”
Section: Discussionmentioning
confidence: 95%
“…Specifically blocking NMDA receptors with (+)-MK 801 reduced Ocdependent bone resorption and actin ring formation in vitro (Chenu et al 1998;Itzstein et al 2000), but this antagonist was ineffective at altering mature Oc activity when added after 7 days of culture (Peet et al 1999). Furthermore, one study reported that (+)-MK 801 inhibited alkaline phosphatase (ALP) activity, an enzyme expressed by Ob during new bone formation (Ho et al 2005). Although suggestive of a more important role for NMDA receptors in differentiation rather than mature cell functions, the potential for indirect effects due to other cells in mixed culture models advocates for a more cautious interpretation.…”
Section: Introductionmentioning
confidence: 99%